Production and development of didactic games in the teaching of Chemistry: Alternative paths adopted in relation to Inclusive Education (Research, Society and Development, 2021)
The appropriation of scientific concepts in Chemistry Teaching is quite expressive, thus, the teacher as a mediator of this process, should propose and develop alternative methodologies, which aim to enhance student learning in the classroom. However, it is necessary to understand which methodological proposals are developed, and which alternative paths are adopted in relation to inclusive education. Thus, this study brings a qualitative bibliographical research, seeking to survey the papers submitted in the annals of the National Meeting of Chemistry (ENEQ), intended for the Exhibition of Teaching Materials for Chemistry (MOMADIQ), involving inclusive teaching practices. The results produced discuss the constitution of collective processes, which reflect the importance of the production and development of didactic games, in the formation of the subject, both in the conceptual basis of scientific knowledge, and in the construction of subjectivity.